Comparative study on effects of Cymbopogon citratus (DC.) Stapf and Mangifera indica (L.) on sperm indices of male albino rats (Nigerian Journal of Physiological Sciences, 2025)
ABSTRACT:The effects of various doses of Cymbopogon citratus (DC.) Stapf and Mangifera indica (L.) ethanolic leaf extract was investigated on fertility of male albino rats. Twenty-five (25) adult male rats were randomly grouped into five (5) cages (n=5). Control rats were given distilled water while experimental groups were daily administered ethanol leaf extract of C. citratus and M. indica through oral gavage at 150 and 300 mg/kg body weight, respectively; for 21 days. After the 21st day of post exposure (PE), experimental animals were sacrificed and their testes extracted and fixed. Sperm count, sperm morphology and sperm motility were assessed. C. citratus extract significantly increased mean sperm count of the treated rats at both 150 mg/kg body weight (272.00±7.47x106/ml) and 300 mg/kg body weight (297.00±3.62) groups, compared to those of M. indica extract (113.20±12.51x106/ml) and (27.60±3.67x106/ml) for 150 and 300 mg/kg body weight, respectively. Also, C. citratus produced a reduction in abnormal sperm morphology (15.20±1.77%) and (17.00±2.00%) for 300 and 150 mg/kg body weight, respectively; compared to M. indica extract (64.00±1.87%) and (51.00±3.32%) for 300 and 150 mg/kg body weight, respectively. M. indica significantly (p